Small theropod teeth from the Late Cretaceous of the San Juan Basin, northwestern New Mexico and their implications for understanding latest Cretaceous dinosaur evolution. - Thomas E Williamson; Stephen L Brusatte (PLoS ONE, 2014)
Studying the evolution and biogeographic distribution of dinosaurs during the latest Cretaceous is critical for better understanding the end-Cretaceous extinction event that killed off all non-avian dinosaurs. Western North America contains among the best records of Late Cretaceous terrestrial vertebrates in the world, but is biased against small-bodied dinosaurs. Isolated teeth are the primary evidence for understanding the diversity and evolution of small-bodied theropod dinosaurs during the Late Cretaceous, but few such specimens have been well documented from outside of the northern Rockies, making it difficult to assess Late Cretaceous dinosaur diversity and biogeographic patterns. We describe small theropod teeth from the San Juan Basin of northwestern New Mexico. These specimens were collected from strata spanning Santonian - Maastrichtian. We grouped isolated theropod teeth into several morphotypes, which we assigned to higher-level theropod clades based on possession of phylogenetic synapomorphies. We then used principal components analysis and discriminant function analyses to gauge whether the San Juan Basin teeth overlap with, or are quantitatively distinct from, similar tooth morphotypes from other geographic areas. The San Juan Basin contains a diverse record of small theropods. Late Campanian assemblages differ from approximately coeval assemblages of the northern Rockies in being less diverse with only rare representatives of troodontids and a Dromaeosaurus-like taxon. We also provide evidence that erect and recurved morphs of a Richardoestesia-like taxon represent a single heterodont species. A late Maastrichtian assemblage is dominated by a distinct troodontid. The differences between northern and southern faunas based on isolated theropod teeth provide evidence for provinciality in the late Campanian and the late Maastrichtian of North America. However, there is no indication that major components of small-bodied theropod diversity were lost during the Maastrichtian in New Mexico. The same pattern seen in northern faunas, which may provide evidence for an abrupt dinosaur extinction.